2005
DOI: 10.1016/j.asj.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Skin biopsy analysis reveals predisposition to stretch mark formation

Abstract: A series of in vitro tests led to the discovery of a dormant phenotype in dermal fibroblasts from patients with stretch marks. The described tests may serve as a diagnostic tool for predicting predisposition to stretch marks. The reported reversibility of impaired fibroblast phenotypes opens a new perspective for preventive treatments for people predisposed to stretch mark formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
1
39
1
Order By: Relevance
“…It has also been reported that exposing human skin to extreme hyperthermia (43°C) results in accumulation of amorphous elastin aggregates resembling those observed in photo-aged skin (31)(32)(33). In contrast, the results of our study indicate for the first time that exposure to 39 or 41°C induces significant enhancement in the deposition of elastic fibers in cultures of normal aortic SMCs, as well as in cultures of dermal fibroblasts derived from normal human skin and from patients affected by an acquired idiopathic elastinopathy that has caused stretch marks (26,27,41,42) or the secondary elastinopathy observed in genetic CS. Because such a mild hyperthermia did not induce up-regulation in the deposition of fibronectin or collagen type I (Fig.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It has also been reported that exposing human skin to extreme hyperthermia (43°C) results in accumulation of amorphous elastin aggregates resembling those observed in photo-aged skin (31)(32)(33). In contrast, the results of our study indicate for the first time that exposure to 39 or 41°C induces significant enhancement in the deposition of elastic fibers in cultures of normal aortic SMCs, as well as in cultures of dermal fibroblasts derived from normal human skin and from patients affected by an acquired idiopathic elastinopathy that has caused stretch marks (26,27,41,42) or the secondary elastinopathy observed in genetic CS. Because such a mild hyperthermia did not induce up-regulation in the deposition of fibronectin or collagen type I (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…Organ Cultures of Explants Derived from Human SkinFragments of normal and stretch-marked skin (26,27) collected during plastic surgery procedures from the stretchmarked skin of three female patients, cases 1, 2, and 3, were cut into multiple 4-mm 2 pieces, placed in culture dishes, and maintained for 5 days at 37 or 41°C in DMEM containing 5% FBS. At the end of this period, all organ cultures were fixed in 1% buffered formalin, and their transverse serial histological sections were stained with Movat's pentachrome (28), which shows elastin as black, glycosaminoglycans as green, collagen as yellow, and cell nuclei as dark blue.…”
Section: Methodsmentioning
confidence: 99%
“…These lesions closely resemble those seen in patients with Cushing's syndrome (Summers et al, 1964) or patients persistently treated with steroids (Chernosky and Knox, 1964). Stretch marks are characterized by a thin epidermis, loss of dermal papillae, loss of rete ridges (Zheng et al, 1985), and a decrease in the net content of collagen, fibronectin (Lee et al, 1994), fibrillin 1 (Watson et al, 1998), and elastic fibers (Mitts et al, 2005). Especially severe and extended loss of elasticity occurs after enzymatic degradation of the elastic fibers in mid-dermal elastolysis (Patroi et al, 2003), elastosis perforans serpiginosa, and cutis marmorata teleangiectasia congenita (Hinek et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
“…Another hypothesis suggests that the formation of SD is related to the reorganization and diminution of dermal elastic fibers network, rather than collagen transformation 13. Excessive mechanical stretching of the skin determines the rupture of the elastic fibers while the fibroblasts are unable to repair the components of the extracellular matrix 14. The quality of fibroblasts is also altered in striae, with a reduction in fibronectin, and type I and type III procollagen expression in fibroblasts from SD 8.…”
Section: Introductionmentioning
confidence: 99%